(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to build an evaluation form for the parts and steps of students’ products in the Department of Family Education and Artistic Professions. The first chapter included the research problem. The researcher tried to answer how to build a model for evaluating artistic outcomes for students of the Department of Family Education and Artistic Professions in carpentry. Search and define the terms in its title.As for the second chapter, it included a section on evaluation and carpentry, and the third chapter contains research procedures and the research community consisting of students from the Department of Family Education and Technical Professions and how to choose the sample. And building the tool, its honesty, stability, and then the evaluation. The study reached several results, including:The result shows that the grades for evaluating the technical outputs of carpentry work at this level are considered acceptable to this extent. It is considered a good level. And the third-year student in the Department of Family Education and Technical Professions studies carpentry principles in the second stage, and advanced carpentry in the third stage. The researcher is good because the students are beginners in the field of wood arts and are not professional carpenters.The most important conclusions are that it is possible to learn carpentry skills and techniques, which is possible in light of the availability of a successful method and the creation of appropriate conditions, as well as recommendations, suggestions and a list of sources.The appendices included the names of the experts and the final form for analyzing the technical productions.